Resistome and microbiome profiling of bovine milk following antimicrobial dry cow therapy: insights from short- and long-read metagenomic sequencing - Urrutia-Angulo, Leire; Lavín, José Luis; Oporto, Beatriz; Aduriz, Gorka; Hurtado, Ana; Ocejo, Medelin (Frontiers in Microbiomes, 2025)
Selective antimicrobial dry cow therapy (DCT) is implemented as part of mastitis control programs, particularly in dairy cows with recent clinical episodes or elevated somatic cell counts. In this study, we investigated the effects of the use of antimicrobials at drying-off on the milk microbiota and resistome by comparing treated (T, n=18) and untreated (NT, n=13) cows. Milk samples from all animals were analyzed using short-read Illumina shotgun sequencing and a subset of 10 samples were also subjected to long-read Oxford Nanopore Technologies (ONT) sequencing. No significant differences in microbial composition or diversity were observed between treated and untreated groups with either technique, indicating that antimicrobial DCT may not induce long-term shifts in the milk microbiota. However, cows receiving antibiotic treatment showed a higher diversity and abundance of genetic determinants of resistance (GDRs) in their milk resistome. Findings from the two sequencing platforms revealed limited concordance in antimicrobial resistance gene content, highlighting that sequencing platform and bioinformatic pipeline choices substantially influence resistome profiling outcomes. Furthermore, the high proportion of host DNA limited sequencing depth and sensitivity, underscoring the need for improved host DNA depletion or targeted enrichment strategies. This study provides insights into the biological and methodological challenges of milk resistome characterization, particularly in low-biomass, host-DNA-rich samples and demonstrates the lack of standardized analytical approaches in resistome studies. Overall, our findings support the prudent use of antibiotics and highlight the need for further longitudinal studies to clarify the temporal dynamics of antimicrobial DCT effects on the milk resistome and microbiota.